Cover Image, Volume 528, Issue 7. Issue 7 (5th March 2020) - Candelario, Kate M.; Balaj, Leonora; Zheng, Tong; Skog, Johan; Scheffler, Bjorn; Breakefield, Xandra; Schüle, Birgitt; Steindler, Dennis A.
Abstract : The cover image is based on the Original Article Exosome/Microvesicle Content is Altered in LRRK2 Mutant iPSCderived Neural Cells by Dennis A. Steindler, Kate M. Candelario, Johan Skog et al., https://doi.org/10.1002/cne.24819 .